A Comparative Study between the Seven Types of Fuel Cells - Guangul, Fiseha M.; Chala, Girma T. (Applied Science and Engineering Progress, 2020)
In the new era with advanced technologies, fuel cell has been widely used as source of power both for portable and stationary applications. The application has become more popular nowadays as it is an eco-friendly device and has no noise due to absence of rotating components. Fuel cells are designed with high efficiency compared to conventional energy sources. However, the benefits have come with weaknesses and threats that might deter its prevalent application. This paper is, therefore, aimed at comparing the seven mainly used fuel cells. The SWOT analysis of the fuel cells are also presented separately, and the pros and cons of each cell were summarized.